Digital and multi-channel citizen participation in Germany: A comprehensive overview of patterns, methods and determinants; Digitale und mehrkanalige Partizipation in Deutschland: Ein umfassender Überblick über Strukturen, Methoden und Determinanten - Sarah Karic; Jan Heissler; Marie-Christin Althaus (Raumforschung und Raumordnung / Spatial Research and Planning, 2024)
Citizen participation has played an increasingly relevant role in spatial planning and development aiming to shape sustainable and innovative processes since the 1970s. Nevertheless, analogue participation is associated with various problems, such as social selectivity and a loss of civic trust in administration and politics. Against this background, high expectations lie in the development of digital participation formats, which have significantly changed the participation landscape. Despite the rapid development of digital participation based on new technologies and external factors such as the Covid-19 pandemic, there is still a lack of comprehensive empirical studies on spatial patterns and determinants. Therefore, the aim of the paper is to give an overview of the patterns, methods and determinants of digital and multi-channel participation in Germany. We comprehensively investigated digital and multi-channel participation processes on the websites of German cities and districts - about 4,000 approaches in total. The results show spatial disparities in digital participation processes. While the availability of broadband internet and public debt do not significantly influence the digital participation density in districts and cities, low election turnouts go along with high densities. This suggests that the administrations are responding to political disinterest with digital participation. The results also indicate that digital participation can be less socially selective, as high shares of population without German citizenship, high migration rates and low employment rates have significant positive effects on digital participation. – – Bürgerbeteiligung spielt seit den 1970er-Jahren in der Raumplanung und -entwicklung eine zunehmend relevante Rolle zur Gestaltung nachhaltiger und innovativer Prozesse. Dennoch ist analoge Partizipation mit Problemen wie sozialer Selektivität und dem Verlust bürgerschaftlichen Vertrauens in Verwaltung und Politik verbunden. Vor diesem Hintergrund liegen hohe Erwartungen in digitalen Beteiligungsformaten, die das Beteiligungsspektrum aufgrund neuer Technologien und externen Faktoren, wie der Covid-19-Pandemie, deutlich verändert haben. Dennoch fehlen bislang umfassende empirische Studien zu räumlichen Mustern und Determinanten. Dieser Beitrag gibt einen Überblick über die Muster, Methoden und Determinanten digitaler und mehrkanaliger Beteiligung in Deutschland. Dazu wurden die Webseiten deutscher Städte und Landkreise umfassend untersucht - insgesamt rund 4.000 Beteiligungsansätze. Die Ergebnisse zeigen räumliche Unterschiede bei digitalen Beteiligungsverfahren.Während die Verfügbarkeit von Breitbandinternet und öffentliche Schulden keinen signifikanten Einfluss auf die Verfahrensdichte in Landkreisen und Städten haben, geht eine niedrige Wahlbeteiligung mit hohen Beteiligungsdichten einher. Dies gibt Hinweise darauf, dass Verwaltungen mit digitaler Partizipation auf politisches Desinteresse reagieren. Die Ergebnisse deuten zudem darauf hin, dass digitale Beteiligung weniger sozial selektiv sein kann, da hohe Bevölkerungsanteile ohne deutsche Staatsbürgerschaft, Migrationsraten und niedrige Beschäftigungsquoten digitale Beteiligungsangebote signifikant positiv beeinflussen.
Keywords: 710; Citizen participation; digital participation; spatial development; spatial planning; Partizipation; digitale Beteiligung; Raumplanung; Raumentwicklung